2018
DOI: 10.1111/acps.12949
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve as an outcome predictor: first‐episode affective versus non‐affective psychosis

Abstract: CR plays a differential role in the outcome of psychoses according to the diagnosis. Specifically, in order to address the needs of non-affective patients with low CR, cognitive rehabilitation treatments will need to be 'enriched' by adding pro-cognitive pharmacological agents or using more sophisticated approaches. However, a functional remediation therapy may be of choice for those with an affective psychosis and low CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 71 publications
12
59
0
Order By: Relevance
“…Other studies also found that cognitive reserve can predict both the risk of illness as symptoms remit and functional improvement (Barnett et al, 2006;Forcada et al, 2015;Grande et al, 2017). Amoretti et al (2016) have shown that cognitive reserve predicts neuropsychological outcome, negative symptoms, and functioning at 2 years of follow-up, and hence, cognitive reserve can be used as a reliable indicator for the course of FEP patients (Amoretti et al, 2018).…”
Section: Psychologicalmentioning
confidence: 96%
“…Other studies also found that cognitive reserve can predict both the risk of illness as symptoms remit and functional improvement (Barnett et al, 2006;Forcada et al, 2015;Grande et al, 2017). Amoretti et al (2016) have shown that cognitive reserve predicts neuropsychological outcome, negative symptoms, and functioning at 2 years of follow-up, and hence, cognitive reserve can be used as a reliable indicator for the course of FEP patients (Amoretti et al, 2018).…”
Section: Psychologicalmentioning
confidence: 96%
“…On one hand, cognitive reserve, defined as the ability of a brain to cope with brain pathology in order to minimize symptoms ( 109 ), may be useful in early stages to predict neurocognitive performance in patients with bipolar disorder ( 110 ), as it has been found that lower estimated cognitive reserve is associated with worse performance in neuropsychological tests and more functional impairment ( 110 , 111 ). Similarly, a recent study on first-episode psychosis has found that those patients with affective psychosis with a greater cognitive reserve showed a higher socioeconomic status, better functioning and greater verbal memory performance ( 112 ). This study also emphasizes the need to explore the impact of specific interventions, like physical activities and hobbies, on cognitive reserve, since it could be useful to guide the development of personalized treatment programs ( 112 ).…”
Section: From Staging To Precision Staging Modelsmentioning
confidence: 99%
“…Similarly, a recent study on first-episode psychosis has found that those patients with affective psychosis with a greater cognitive reserve showed a higher socioeconomic status, better functioning and greater verbal memory performance ( 112 ). This study also emphasizes the need to explore the impact of specific interventions, like physical activities and hobbies, on cognitive reserve, since it could be useful to guide the development of personalized treatment programs ( 112 ). Therefore, cognitive enhancing strategies might be key in the early stages and not necessarily in the late stages of the disease.…”
Section: From Staging To Precision Staging Modelsmentioning
confidence: 99%
“…The concept of cognitive reserve may provide an explanation for the discrepancy in these results since it reflects the capacity of the brain to endure neuropathology and successfully complete cognitive tasks ( 69 ). Moreover, cognitive reserve has been found as a significant predictor of cognitive and psychosocial functioning in patients with SZ and BD ( 70 72 ). Another key issue in CR interventions relates to the relationship between number of sessions and the obtained benefits.…”
Section: Discussionmentioning
confidence: 99%